Exploring the Slum Formation in Medan: A Literature Review in Urban Planning and Society - Suci Astari; Adinda Juwita Nasution (Abdul Media Literasi, 2024)
This article delves into the intricate issue of slum formation in Medan, Indonesia, exploring the challenges and opportunities in addressing this pressing urban problem. Drawing from a comprehensive literature review in urban planning and society, it elucidates the multifaceted factors contributing to the emergence of slums in Medan. These factors include high urbanization rates, limited access to basic amenities, low socioeconomic conditions, and inadequate spatial planning. Moreover, the article examines the adverse impacts of slum areas on both society and the environment, encompassing social, economic, and environmental ramifications. Despite facing complex challenges, there are opportunities to enhance the effectiveness of slum area mitigation programs in Medan. Collaborative efforts across sectors, utilization of technology, and community empowerment emerge as pivotal strategies in tackling this issue. Through strong partnerships among government agencies, NGOs, the private sector, and local communities, along with the application of innovative technological solutions in planning and implementation, a more holistic and integrated approach to slum area mitigation can be achieved. In emphasizing the importance of a comprehensive and sustainable approach to addressing slum areas, this article underscores the significance of collective action in designing solutions. By leveraging collaborative efforts and innovative approaches, it aims to foster the creation of inclusive, sustainable, and humane urban environments for all residents of Medan.